Comunicación Organizacional Interna y su Relación con la Satisfacción de los Empleados de una Empresa Concesionaria de Automóviles de Piedras Negras Coahuila (2020)
Communication within an organization is of the utmost importance since through it the strategies are deployed in order that all its workers reach the company objectives. The objective of this investigation is to analyze how this internal communication relates to the satisfaction of the employees and their superiors of the Piedras Negras Coahuila car dealership. This study is descriptive and correlational, a survey was used to collect the perceptions of all employees if the company. The result of the investigation shows that the employees are satisfied with the internal communication that takes place between the same colleagues as well as with their superiors